نهج القرآن الكريم في نصرة النبي صلى الله عليه وسلم سورة التوبة أنموذجا دراسة موضوعية - نوبلي, عواطف; مناني, ماجدة (University of eloued جامعة الوادي, 2021)
" يتضمن هذا البحث دراسة موضوعية لعنوان: نهج القرآن الكريم في نصرة النبي ﷺ سورة التوبة أنموذجا. وهو موضوع قرآني ومعاصر مهم. وقد اشتمل بحثنا هذا على مبحثين: مبحث نظري ومبحث تطبيقي. ولدراسة هذا البحث قسمنا العمل إلى: مقدمة؛ بينا فيها بعض منهجنا في العمل، يليها المبحث الأول المرسوم ب: التعريف بمصطلحات البحث، وثانٍ معنونٍ ب: نهج القرآن الكريم في نصرة النبي ﷺ. وفي الختام ختمنا بخاتمة ذكرنا فيها بعض النتائج والتوصيات التي توصلنا إليها من خلال دراستنا هذه. "This research includes an objective study titled: The prophet Muhammed (Peace be upon him) advocacy according to The Nobel Quran path, Surat Al-Tawbah as a model. which is an important contemporary subject. Our research includes two themes: theoretical and practical. the research study was divided into an introduction; where we clarified some of our work approaches, then the first theme was designed for defining the research terminologies, and the other titled by The prophet Muhammed(Peace be upon him) advocacy according to The Nobel Quran path. Finally, some of the results and recommendations were mentioned that we reached through our study.
علوم قرآن
Keywords: نهج. نصرة. النبي صلى الله عليه وسلم. القرآن الكريم. السورة التوبة.; APPROACh. victory. Prophet peace be upon him. The Holy Quran. SUraa Tawbaa